The Effects of Exchange rate on the Trade Balance in the Sri Lankan Context after Post Liberalization. - Vijayakumar, S. (International Journal on Global Business Management and Research, 2014)
Generally the developing countries have relied on devaluation of exchange rate as a tool in enhancing the trade balance and balance of payment. This is not different in the case of Sri Lanka. The study is based on two country model involving trade between Sri Lanka and the U.S.A. This study is based on secondary time series data from 1977 to 2010. The model I have recourse to is a model adopted by many researchers where the trade balance and real exchange rate are directly linked. The analysis is done by the use of statistical package Eviews includes the econometric procedures of Unit root test, Engle - Granger and Johansen technique for co- integration and also IRF analysis to test J curve effect along with multiple regression analysis. The aim of the study is to scrutinize the relationship among trade balance, real exchange rate and real income and to find out whether there is existence of J curve in the bilateral trade between Sri Lanka and United State. Several literatures in regard to the relationship between trade balance and exchange rate effect in globe shows fact that some empirical studies supported J curve and some other studies is did not. Similarly, Some Economists clearly mentioned that the devaluation may work better for industrialized countries than for developing countries. Many developing countries are exporting the commodities that are in elastic. Their price elasticity is less than one or in elastic. But they are importing the commodities that have inelastic demand. Therefore, devaluation of exchange rate does not produce a favorable effect on trade balance of developing countries. In case of Sri Lanka, The unit root test confirms that all variables make the series stationary. Therefore it can be stated that all variables are integrated of order 1. The Engle- Granger methodology has revealed that the variable in the model 1 are co integrated implying that a long run relationship exists between the variables. It is clear the fact that IRF analysis does not show any sign of the J curve. In brief, the result suggests that variables In TB, In RER, In RSL and In RUS are co- integrated. The result brings to light the fact that the real exchange rate has significantly positive influence on the trade balance of Sri Lanka both in the short- run and the long-run. However, evidence of J curve effect is non existence for trade between Sri Lanka and USA. The devaluation improving the trade balance in the short- run has repetitive tendency in the long-run.
Keywords: Trade balance; Balance of payment; J curve; Devaluation; Real exchange rate